2021
DOI: 10.1002/anie.202013731
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Chemically and Biologically Diverse Pyrroquinoline Pseudo Natural Products

Abstract: Natural product (NP) structures are a rich source of inspiration for the discovery of new biologically relevant chemical matter. In natural product inspired pseudo‐NPs, NP‐derived fragments are combined de novo in unprecedented arrangements. Described here is the design and synthesis of a 155‐member pyrroquinoline pseudo‐NP collection in which fragments characteristic of the tetrahydroquinoline and pyrrolidine NP classes are combined with eight different connectivities and regioisomeric arrangements. Cheminfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…For each of the different connectivity/regioisomeric arrangements of the pyrroquinolines (Scheme 2 d), distinct phenotypic outcomes were observed in the CPA [38] . This work showed that differential combination of a confined set of NP‐fragments can provide scaffolds that exhibit diverse biological activity patterns.…”
Section: Biological Evaluation Of Pseudo‐np Librariesmentioning
confidence: 78%
See 1 more Smart Citation
“…For each of the different connectivity/regioisomeric arrangements of the pyrroquinolines (Scheme 2 d), distinct phenotypic outcomes were observed in the CPA [38] . This work showed that differential combination of a confined set of NP‐fragments can provide scaffolds that exhibit diverse biological activity patterns.…”
Section: Biological Evaluation Of Pseudo‐np Librariesmentioning
confidence: 78%
“…[65] This finding suggests that novel combinations of NP fragments in nature can be induced, and that the current repertoire of known NPs,i np rinciple,c an be complemented by existing,b ut maybe currently not actively or differently used biosynthetic pathways.B ya nalogy,N P fragments could be employed as "inheritable building blocks" in an ew,e volutionary strategy towards bioactive compound discovery.I nt his strategy,t he novel combination of NPfragments by biosynthetic steps as described above would be replaced by synthetic fragment combinations leading to pseudo-natural products.T hese pseudo-NPs currently have not been identified from natural sources,b ut the example described above suggests that, in principle,t hey may be amenable to biosynthesis.A lso,i ti sp ossible that they may indeed exist in nature but have not been identified yet. In fact, after the pyrroquinoline scaffold 38 had been synthesised in the context of ap seudo-NP program, [38] the scaffold was reported to occur in nature in the NP Albogrisin. [66] Evolutionary optimisation requires that genotypes are varied by recombination and/or mutation,a nd their phenotypes are sorted under specific constraints.The best-performing phenotypes ("the fittest") are selected because they confer an advantage,f or example,i mproved molecular recognition or effector features.Since the fittest descendants have ag enotype (= hereditary information) that was not present before,evolution can also be understood as aprocess during which new information is continually generated.…”
Section: Chemical Evolution Of Np Structurementioning
confidence: 99%
“…For each of the different connectivity/regioisomeric arrangements of the pyrroquinolines (Scheme 2 d ), distinct phenotypic outcomes were observed in the CPA. [38] This work showed that differential combination of a confined set of NP‐fragments can provide scaffolds that exhibit diverse biological activity patterns. Morphological screening of the pseudo‐NP library described in Scheme 3 in the CPA revealed that a large proportion of compounds were bioactive.…”
Section: Biological Evaluation Of Pseudo‐np Librariesmentioning
confidence: 95%
“…Also, it is possible that they may indeed exist in nature but have not been identified yet. In fact, after the pyrroquinoline scaffold 38 had been synthesised in the context of a pseudo‐NP program, [38] the scaffold was reported to occur in nature in the NP Albogrisin. [66] …”
Section: Chemical Evolution Of Np Structurementioning
confidence: 99%
“…To fill this gap, several creative strategies have been developed to rapidly generate complex compounds, including construction of natural product‐inspired scaffolds, [20–24] diversity‐oriented synthesis (DOS) [25–28] and biology‐oriented synthesis (BIOS) [29–31] . Inspired by nature, we have reported a complementary strategy named Complexity‐to‐Diversity (CtD).…”
Section: Introductionmentioning
confidence: 99%